Challenges and opportunities of CNG conversion business of Rahimafrooz Gastech Limited - Zohora, Fatema Tuz (BRAC University, 2013)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2012.